Sistema de riego, calefacción automatizados y monitoreo de variables ambientales, mediante IOT en invernaderos del sector florícola, para la empresa Horti Jardines S.A. - Ávila Araque, Alexis Guillermo (2023)
The project was designed for Hortijardines S.A., a floricultural company specializing in growing roses. In this field, constant monitoring of the climatic conditions inside the greenhouse is crucial to prevent problems such as diseases or pests. Optimal irrigation and adequate heating are essential to maximize rose production and quality. The main purpose of this system is to provide continuous monitoring of the greenhouse. It uses sensors and microcontrollers to automate and manage irrigation and heating, allowing precise control over climatic variables. This automation seeks to maintain the greenhouse in ideal conditions for optimal rose development. All of this can be supervised through a web system allowing better crop management. This development was based on documentary and bibliographic research, complemented by direct observations. From these investigations, the essential requirements for the project were identified and the most pertinent tools for its development were determined.